A dystroglycan-laminin-integrin axis coordinates cell shape remodeling in the developing Drosophila retina. - Rhian F Walther; Courtney Lancaster; Jemima J Burden; Franck Pichaud (PLoS Biology)
Cell shape remodeling is a principal driver of epithelial tissue morphogenesis. While progress continues to be made in our understanding of the pathways that control the apical (top) geometry of epithelial cells, we know comparatively little about those that control cell basal (bottom) geometry. To examine this, we used the Drosophila ommatidium, which is the basic visual unit of the compound eye. The ommatidium is shaped as a hexagonal prism, and generating this 3D structure requires ommatidial cells to adopt specific apical and basal polygonal geometries. Using this model system, we find that generating cell type-specific basal geometries starts with patterning of the basal extracellular matrix, whereby Laminin accumulates at discrete locations across the basal surface of the retina. We find the Dystroglycan receptor complex (DGC) is required for this patterning by promoting localized Laminin accumulation at the basal surface of cells. Moreover, our results reveal that localized accumulation of Laminin and the DGC are required for directing Integrin adhesion. This induces cell basal geometry remodeling by anchoring the basal surface of cells to the extracellular matrix at specific, Laminin-rich locations. We propose that patterning of a basal extracellular matrix by generating discrete Laminin domains can direct Integrin adhesion to induce cell shape remodeling in epithelial morphogenesis.